2000
DOI: 10.1556/aphysiol.87.2000.1.8
|View full text |Cite
|
Sign up to set email alerts
|

A chloroform extract obtained from a decoction of Ficus carica leaves improves the cholesterolaemic status of rats with streptootocin-includede diabetes

Abstract: The antidiabetic effects of Ficus carica leaf extracts have been reported previously. From the aqueous decoction of fig leaves, after treatment with HCI, centrifuging, treatment with sodium hydroxide (NaOH) and extraction with chloroform (CHCl3), the administration of the organic phase rats with streptozotocin-induced diabetes led to a decline in the levels of total cholesterol and an decrease in the total cholesterol/HDL cholesterol ratio (with respect to the control group), together with a reduction of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…Medium average capillary profiles were also lower in patients during Ficus carica therapy versus non-sweet commercial tea. Average insulin dose was 12% lower during Ficus carica therapy in the total group [114].The aqueous decoction of fig leaves was treated with HCI, centrifuged, treated with sodium hydroxide (NaOH) and extracted with chloroform, the administration of the organic phase to rats with streptozotocin-induced diabetes led to a decline in the levels of total cholesterol and decrease in the total cholesterol/HDL cholesterol ratio compared to control group, together with a reduction of the hyperglycaemia [115].…”
Section: Antidiabetic Effectmentioning
confidence: 99%
“…Medium average capillary profiles were also lower in patients during Ficus carica therapy versus non-sweet commercial tea. Average insulin dose was 12% lower during Ficus carica therapy in the total group [114].The aqueous decoction of fig leaves was treated with HCI, centrifuged, treated with sodium hydroxide (NaOH) and extracted with chloroform, the administration of the organic phase to rats with streptozotocin-induced diabetes led to a decline in the levels of total cholesterol and decrease in the total cholesterol/HDL cholesterol ratio compared to control group, together with a reduction of the hyperglycaemia [115].…”
Section: Antidiabetic Effectmentioning
confidence: 99%
“…FC decoction may improve lipid (16,17) and antioxidant profiles (18) of the patients with DM. Meanwhile, studies on hypoglycemic effect of F. carica (FC) are limited to one study on rats with diabetes (20) and one study on 10 insulin-dependent humans (21).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported therapeutic effects of decoction of Ficus carica leaves (common fig) on lipid (16,17) and antioxidant profiles (18) of patients with diabetes . Meanwhile, Rashidi and Noureddini in their study fed the rats with diabetes with F. carica leaves extract for four days and then results showed that glucose tolerance improved compared to the control group.…”
Section: Introductionmentioning
confidence: 99%
“…The dragon fruit helps the digestive process, prevent colon cancer and diabetes, neutralize toxic substances such as heavy metal, reduce cholesterol levels and high blood pressure and consumed regularly the dragon fruit can help against asthma and cough. (2) It is also rich with potassium, protein, fiber, sodium and calcium which goods for health than other fruits Watermelon Watermelon (citrullus lanatus) is a great source of potassium, and extremely low in sodium. Natural sources of potassium help the heart and is beneficial for patients with high blood pressure.…”
Section: Dragon Fruitmentioning
confidence: 99%